Synthesis of an inhibitor of carbonic anhydrase : formulation of an inhibitor of carbonic anhydrase : formulation of δ-aminolevulinic acid for melanoma imaging - Nascimento, Hugo Guimarães (2017)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014